LILRA3 deletion is a genetic risk factor of HIV infection. (2nd January 2017) - Ahrenstorf, Gerrit; Low, Hui Zhi; Kniesch, Katja; Ordonez, David; Meyer-Olson, Dirk; Ahmad, Fareed; Kücherer, Claudia; Gunsenheimer-Bartmeyer, Barbara; Stoll, Matthias; Matthias, Torsten; Schmidt, Reinhold E.; Witte, Torsten
Abstract : Objective: The aim of this study is to analyse the influence of LILRA3 and the genetic leukocyte immunoglobulin-like receptor 3 (LILRA3) deletion on transmission and clinical course of HIV infection. Design: Case and control study. Methods: LILRA3 genotypes were determined by PCR. HIV patients were categorized into short-term progressors, normal progressors and long-term nonprogressors according to the clinical course. Functional studies were performed using real-time PCR, intracellular flow cytometry and ELISA. Results: The prevalence of the homozygous LILRA3 deletion was higher in HIV-positive individuals ( n = 439) than in controls ( n = 651) ( P = 0.02). The disease progression was faster in homozygously deleted patients with more short-term progressors than in heterozygous ( P = 0.03) and homozygously positive ( P = 0.002) individuals. These results have been confirmed in a seroconverter cohort ( n = 288). The frequency of the homozygous deletion in the confirmation cohort was higher than in controls ( P = 0.04). Combining both cohorts, the proportion of homozygously LILRA3-deleted individuals was 6.2% in HIV-infected patients ( n = 727) vs. 3.2% in controls ( P = 0.01). Functional analysis revealed an upregulation of the LILRA3 gene in real-time PCR in treated patients when compared with untreated patients ( P = 0.007) and controls ( P = 0.02) resulting in a higher LILRA3 expression in CD4 + ( P = 0.008) and CD14 + ( P = 0.02) cells of untreated patients in intracellular flow cytometry. LILRA 3 concentrations in the sera were similar between the groups, in untreated patients a correlation between viral load and LILRA3 concentration was found. Conclusion: The homozygous LILRA3 deletion is associated with a higher susceptibility for HIV disease and with a faster disease progression.